99mTc-DPD scintigraphy in immunoglobulin light chain (AL) cardiac amyloidosis. (13th July 2021) - Quarta, Candida Cristina; Zheng, Jiexin; Hutt, David; Grigore, Simona F; Manwani, Richa; Sachchithanantham, Sajitha; Mahmood, Shameem A; Whelan, Carol J; Fontana, Marianna; Martinez-Naharro, Ana; Chacko, Liza; Lachmann, Helen J; et al.
Abstract: Aims: Technetium-99m-labelled 3, 3-diphosphono-1, 2-propanodicarboxylic acid ( 99m Tc-DPD scintigraphy) is recognized as highly accurate for the non-invasive diagnosis of transthyretin (ATTR) cardiac amyloidosis (CA). A proportion of patients with immunoglobulin light chain (AL) CA have also been reported to show cardiac 99m Tc-DPD uptake. Herein, we assessed the frequency and degree of cardiac 99m Tc-DPD uptake and its clinical significance among patients with AL CA. Methods and results: Between 2010 and 2017, 292 consecutive patients with AL CA underwent 99m Tc-DPD scintigraphy and were included in this study: 114 (39%) had cardiac 99m Tc-DPD uptake: grade 1 in 75%, grade 2 in 17%, and grade 3 in 8% of cases. Patients with cardiac 99m Tc-DPD uptake had poorer cardiac systolic function and higher N-terminal pro-brain natriuretic peptide. No differences were noted in cardiac magnetic resonance parameters between patients with and without cardiac 99m Tc-DPD uptake ( N = 19 and 42, respectively). Patients with cardiac 99m Tc-DPD uptake showed a trend to worse survival than those with no uptake (log-rank P = 0.056). Among 22 patients who underwent serial 99m Tc-DPD scintigraphy, 5 (23%) showed reduction in the grade of cardiac uptake. Conclusions: In this large cohort of patients with AL CA, 99m Tc-DPD scintigraphy ∼40% of cases showed cardiac uptake, including grade 2–3 in 10% of all patients (25% of those with cardiac 99m Tc-DPD uptake). Cardiac 99m Tc-DPD uptake was associated with poorer cardiac function and outcomes. These data highlight the critical importance of ruling out AL amyloidosis in all patients with cardiac 99m Tc-DPD uptake to ensure such patients are not assumed to have ATTR CA.